Juridical Review of Income Tax Restitution (PPH) against Cancellation of Sale and Purchase Agreement Based on Government Regulation Number 34 of 2016 - Alannuari Afid Amasi; Akhmad Khisni; Amin Purnawan (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
The purpose of this study is to analyze: 1) The legal construction of the Sale and Purchase Binding Agreement which is the basis for the imposition of Income Tax (PPh). 2) Implementation of Sale and Purchase Agreement on Land Rights Related to the Imposition of Income Tax (PPh). 3) Procedure for Income Tax (PPh) refunds for the cancellation of the sale and purchase agreement based on Government Regulation Number 34 of 2016. The research resultsare: 1) The legal construction of the Sale and Purchase Agreement which is the basis for the imposition of Income Tax (PPh) is Income Tax Act Number 36 Of 2008 Article 4 paragraph 2 letter d. In this article, it is clearly stated that income obtained from transactions of transfer of rights to land and / or buildings may be subject to final income tax. The rate of Final Income Tax Article 4 paragraph 2 from transactions for the transfer of rights to land and / or buildings in general is 5%. Meanwhile, the tax object is the income obtained from the transaction. 2). The implementation of the sale and purchase agreement on land rights related to the imposition of income tax (PPh) must be carried out in a clear manner, namely based on the agreement of both parties, and carried out with a PPAT deed, in this case a sale and purchase deed (AJB), after the requirements both material and formal have been met. 3. The Income Tax (PPh) restitution procedure for the cancellation of the sale and purchase agreement based on Government Regulation Number 34 of 2016, namely reporting, document verification, administrative research.The consequences of administrative sanctions in the form of an increase of 100% from the basis of tax determination if based on the results of the examination found a lack of tax payments.